Genetic characterization of Colombian indigenous sheep - Ocampo, Ricardo J.; Martínez, Rodrigo A.; Rocha, Juan F.; Cardona, Henry (Revista Colombiana de Ciencias Pecuarias, 2017)
Background: indigenous breeds are important for poor farmers because of their natural selection against harsh environments and adaptation to regional conditions. However, inbreeding of indigenous sheep populations has increased in Colombia due to indiscriminate cross-breeding with foreign animals and lack of reproductive controls, with subsequent loss in productivity, which poses a great risk for the conservation of valuable genes. Objective: to determine the genetic diversity in Colombian indigenous sheep by using a panel of 10 microsatellite molecular markers. Methods: blood samples from 362 individuals from 43 farms in 11 Colombian provinces were genotyped and analyzed for a panel of 10 microsatellite markers. Results: a total of 134 alleles were found (13.4 alleles/locus on average) with a range of observed and expected heterozygosity of 0.428 to 0.831 and 0.615 to 0.855, respectively, and 0.742 polymorphic information content (PIC). The average Wright F-statistics (FIS) of the breeds was 0.107, suggesting moderate levels of inbreeding. Colombian sheep showed a low level of genetic differentiation among breeds (FST = 0.054) and STRUCTURE analysis showed complex patterns of admixture in the breeds. Conclusion: overall, Colombian sheep have high genetic variability, which is very important for future conservation programs and genetic improvement.